The Effect of Heat-Killed Candida Albicans and Dentin Powder on the Antibacterial Activity of Chlorhexidine Solution - Zahed Mohammadi; Sousan Shalavi (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2012)
Introduction: The purpose of this study was to compare the inhibitory effect of heat-killed Candida albicans and dentin powder on the antibacterial activity of chlorhexidine (CHX) against Enterococcus faecalis and Streptococcus sanguis. Materials and Methods: The antibacterial effect of each group was determined by measuring the zone of inhibition diameter in millimeters after incubation at 37°C for 24 hours in a humid atmosphere. Each test was repeated three times. Data were analyzed using ANOVA and Tukey's test. Results: Results indicated that both heat-killed C. albicans and dentin powder decreased the antibacterial activity of CHX against both tested bacteria significantly (P<0.05). Conclusion: In conclusion, both heat-killed Candida albicans and dentin powder reduced the antibacterial activity of CHX significantly.